Meninjau Perlakuan Akuntansi Pelaku UMKM Batik Murni atas Produk Cacat dan Rusak - Alma Athif Fabian; Diah Hari Suryaningrum (Politeknik Negeri Padang, 2025)
Defective and damaged products are often seen as a burden in the production process, but if handled according to the appropriate accounting guidelines, both can have a value that can be optimized. This research aims to review how the treatment of defective and damaged products is applied in UMKM Batik Murni. The results of the study indicate that the lack of classification and systematic accounting records leads to losses that are not clearly identified. The method used in this research is a qualitative research approach. The data collection methods in this study are interviews, observations, documentation, and literature studies. This research uses descriptive analysis methods as a data analysis technique, which involves describing the findings obtained from interviews with the business owner.